Fathers' help seeking behavior and attitudes during their transition to parenthood. Issue 5 (1st August 2022) - Ghaleiha, Amin; Barber, Carrie; Tamatea, Armon J.; Bird, Amy
Abstract: New fathers face multiple changes as they take on this complex, demanding, and continually shifting role. The current study aimed to understand these experiences, especially the ways fathers seek help and information while facing stressful situations. Eleven fathers completed a semi‐structured interview about their transition to fatherhood and whether and how they sought help and advice through that process. Results were analyzed using an inductive thematic analysis approach. Fathers viewed themselves as supportive figures and sources of financial and emotional stability for their families. Fathers experienced anxiety and uncertainty in their transition to parenthood, and utilized a variety of ways to cope with their stress; these were categorized into individual and interpersonal coping strategies. Most relied on their partner for emotional support, but some felt uncomfortable relying on her and using her for support while she was coping with pregnancy and new parenting. This study found that fathers tended to see themselves in a rather traditional role of provider and supporter of their partners and children, and this created some stresses for work‐life balance, and, for some, created a dilemma where they felt unable to seek emotional support from the person—their partner—on whom they would typically rely. These findings have important implications for fathers' wellbeing and providing support programs for new fathers. Resumen: Papás novatos enfrentan múltiples retos a medida que asumen este papel complejo y exigente. Poco se sabe acerca de cómo los papás experimentan estos retos. Este estudio se propuso comprender estas experiencias, especialmente la manera como los papás buscan ayuda e información mientras que enfrentan situaciones estresantes. Once papás completaron una entrevista semiestructurada acerca de la transición a la paternidad y cómo buscaron ayuda a través de ese proceso. Los resultados se analizaron usando un análisis temático inductivo. Los papás se vieron a sí mismos como figuras de apoyo y fuentes de estabilidad económica y emocional para sus familias. Los papás experimentaron ansiedad en la transición a la paternidad y utilizaron diferentes maneras para arreglárselas con el estrés; estas maneras fueron categorizadas en estrategias individuales e interpersonales para arreglárselas. La mayoría confió en sus parejas para apoyo emocional, pero algunos se sintieron incómodos confiando en ella para ese apoyo mientras que ella se las arreglaba con el embarazo y la nueva crianza. En este estudio se encontró que los papás tendían a verse a sí mismos en un papel tradicional de proveer y de apoyar a sus familias, y esto produjo cierto estrés para equilibrar la vida laboral, así como un dilema en los casos en que se sintieron incapaces de buscar el apoyo emocional de sus parejas en quienes ellos confiaban típicamente. Estos resultados tienen implicaciones importantes para el bienestar de los papás y proveer programas de apoyo para los nuevos papás. Résumé: Les nouveaux pères font face à de nombreux défis quand ils embrassent ce rôle complexe et difficile. On sait peu de choses sur la façon dont les pères vivent ces défis. Cette étude s'est donné pour but de comprendre ces expériences, surtout les manières dont les pères cherchent de l'aide et des renseignements tout en faisant face à des situations stressantes. Onze pères ont rempli un entretien semi‐structuré sur leur transition la paternité et la manière dont ils ont cherché de l'aide au travers de ce processus. Les résultats ont été analysés en utilisant une analyse thématique inductive. Les pères se sont perçus comme des figures de soutien et des sources de stabilité financière et émotionnelle pour leur famille. Les pères ont fait l'expérience d'anxiété dans leur transition à la parentalité et ont utilisé différentes manières de faire face au stress; celles‐ci ont été catégorisées en stratégies d'adaptation individuelles et interpersonnelles. La plupart se sont appuyés sur leur partenaire pour le soutien émotionnel, mais certains d'entre eux n'étaient pas l'aise de compter sur elle pour du soutien alors qu'elle faisait face à la grossesse et au nouveau parentage. Cette étude a trouvé que les pères avaient tendance à se voir dans un rôle traditionnel de père pourvoyeur et de soutien pour leur famille et cela déclenchait des stress pour l'équilibre travail‐vie de faille, et un dilemme s'est avéré être qu'ils se sentaient incapables de chercher du soutien émotionnel auprès de leur partenaire sur qui ils compteraient typiquement. Ces résultats ont des implications importantes pour le bien‐être des pères et la création de programmes de soutien aux nouveaux pères. Zusammenfassung: Wie man zum Vater wird: Eine Exploration des Weges in die Vaterschaft neuseeländischer Männer Junge Väter stehen vor zahlreichen Herausforderungen, wenn sie die komplexe und anspruchsvolle Vaterrolle übernehmen. Es ist wenig darüber bekannt, wie Väter diese Herausforderungen erleben. Diese Studie zielte darauf ab, diese Erfahrungen zu verstehen, und zwar insbesondere die Art und Weise, wie Väter in Stresssituationen nach Hilfe und Informationen suchen. Elf Väter absolvierten ein halbstrukturiertes Interview über ihren Rollenwechsel zur Vaterschaft und wie sie in diesem Prozess Hilfe suchten. Die Ergebnisse wurden mithilfe einer induktiven thematischen Analyse ausgewertet. Väter betrachteten sich als unterstützende Figur und Quelle finanzieller und emotionaler Stabilität für ihre Familie. Väter erlebten Angst beim Rollenwechsel zur Elternschaft und nutzten unterschiedliche Wege, um mit Stress umzugehen ‐ diese wurden in individuelle und zwischenmenschliche Bewältigungsstrategien eingeteilt. Die meisten verließen sich auf ihre Partnerin, um emotionale Unterstützung zu erhalten. Einige Väter fühlten sich allerdings unwohl dabei, sich auf die Unterstützung ihrer Partnerin zu verlassen, während diese mit der Schwangerschaft und ihrer neuen Elternrolle zurechtkommen musste. Die Studie ergab, dass Väter sich in der Regel in einer traditionellen Rolle des Versorgers und Unterstützers ihrer Familie sehen. Dies kann zu einer Belastung der Work‐Life‐Balance und dem Dilemma führen, dass sich Väter keine emotionale Unterstützung von ihrer Partnerin suchen, auf die sie sich sonst verlassen. Diese Ergebnisse haben wichtige Implikationen das väterliche Wohlbefinden und für Unterstützungsprogramme für junge Väter. 抄録: 父親になること:ニュージーランドの男性の父性への道のりを探る 初めて父親になると、複雑で要求の多い役割を引き受けることになり、様々な課題に直面することになる。これらの課題を父親がどのように経験するかについては、ほとんど知られていない。本研究は、これらの経験、特にストレスの多い状況に直面しているとき父親が支援や情報を求める方法を理解することを目的とした。11人の父親が、父親になる移行とその過程を通じてどのように支援を求めたかについて、半構造化面接を受けた。結果は帰納的主題分析により解析された。父親は、自分自身を家族の支えとなる存在であり、経済的、情緒的安定の源であるとみなしていた。父親は、親になる移行期に不安を経験し、ストレスに対処するためにいろいろな方法を活用しており、これらの対処方法は個人的対処方法と対人的対処方法に分類された。ほとんどの人が精神情緒的な支えとしてパートナーを頼りにしていたが、相手が妊娠や初めての子育てに対処しようとしている中で頼るということに気まずさを感じるという人もいた。本研究で、父親たちは、家族を養い支えるという伝統的な役割の中に自分自身をみる傾向にあり、 そのことが、仕事と生活のバランス上にストレスを引き起こし、通常は頼れるパートナーに精神情緒的な支えを求められないというジレンマを生み出しているということが分かった。これらの知見は、父親の幸福や、初めて父親になる人への支援プログラムの提供に重要な示唆を与えるものである。 摘要: 新任父亲在承担这一复杂而苛刻的角色时面临着多重挑战。关于父亲如何经历这些挑战, 我们知之甚少。本研究旨在了解这些经历, 尤其是父亲在面临压力时寻求帮助和信息的方式。11位父亲完成了一项半结构化访谈, 内容是关于他们向父亲身份的转变, 以及他们如何在这个过程中寻求帮助。结果采用归纳主题分析法进行分析。父亲们认为自己是家庭经济和情感稳定的支柱与来源。父亲在转变为父母的过程中会感到焦虑, 他们会使用不同的方式来应对压力;这些策略分为个人应对策略和人际应对策略。大多数父亲依赖伴侣的情感支持, 但也有些人在伴侣应对怀孕和养育新子女时, 会对依赖她的支持感到不舒服。这项研究发现, 父亲倾向于将自己视为家庭的提供者和支持者的传统角色, 这给工作和生活的平衡带来了一些压力, 并陷入了一种困境, 使他们感到无法从通常依赖的伴侣那里寻求情感支持。这些发现对父亲的健康以及为新任父亲提供支持计划具有重要意义。 ملخص: الانتقال إلى الأبوة: استكشاف رحلة الرجال النيوزيلنديين نحو الأبوة يواجه الآباء الجدد تحديات متعددة أثناء توليهم هذا الدور المعقد والمتطلب. لا يُعرف سوى القليل عن الكيفية التي يواجه بها الآباء هذه التحديات. هدفت هذه الدراسة إلى فهم هذه التجارب ، لا سيما الطرق التي يلتمس بها الآباء المساعدة والمعلومات أثناء مواجهة المواقف العصيبة. أكمل أحد عشر أبًا مقابلة شبه منظمة حول انتقالهم إلى الأبوة وكيف طلبوا المساعدة خلال هذه العملية. تم تحليل النتائج باستخدام التحليل الموضوعي الاستقرائي. اعتبر الآباء أنفسهم شخصيات داعمة ومصادر للاستقرار المالي والعاطفي لأسرهم. عانى الآباء من القلق أثناء انتقالهم إلى الأبوة واستخدموا طرقًا مختلفة للتعامل مع التوتر ؛ تم تصنيفها في استراتيجيات المواجهة الفردية والشخصية. اعتمد معظمهم على شريكهم للحصول على الدعم العاطفي ، لكن البعض شعر بعدم الارتياح للاعتماد على الشريكة للحصول على الدعم أثناء تأقلمها مع الحمل والرعاية الوالدية الجديدة. وجدت هذه الدراسة أن الآباء يميلون إلى رؤية أنفسهم يلعبون دورًا تقليديًا كمعيلين وداعمين لأسرهم ، وقد خلق هذا بعض الضغوط على التوازن بين العمل والحياة ، ومعضلة شعورهم بأنهم غير قادرين على طلب الدعم العاطفي من شريكهم الذي يعتمدون عليه عادة. هذه النتائج لها آثار مهمة على رفاهية الآباء وتقديم برامج الدعم للآباء الجدد.